Sustainability in International Business (2022)
In a context best characterized by uncertainty and volatility, it is necessary to rethink the key concepts and assumptions underpinning the broad debate on international business. In brief, the world is more interconnected than ever, yet—as the cases of COVID-19 and the war in Ukraine confirm—supply chains are not immune to developments in politics and society. Other factors weigh in on the analysis too. Moreover, as the context in which businesses operate is ever more competitive, traditional approaches to building a competitive edge and succeed in foreign markets need to be reconsidered. Talent management might be the missing link. Hence, this book makes a case for a more direct engagement of the research community with this topic.